Improving exposure of intrusion deception system through implementation of hybrid honeypot - Mansoori, Masood; Zakaria, Omar; Gani, Abdullah (Zarqa University, Jordan, 2012)
This paper presents a new design hybrid honeypot to improve the exposure aspect of intrusion deception systems and in particular, research server honeypots. A major attribute in the design of a server honeypot is its passiveness, which allows the honeypot to expose its services and passively wait to be attacked. Although passiveness of a server honeypot simplifies the analysis process by classifying traffics as malicious, however it also lessens its ability to lure attackers through exposure of vulnerable service. As a result it captures smaller amount of data on attacks for analysis. Client honeypot designs, on the other hand, contain modules that actively interact with outside networks, expose vulnerabilities in client side software, and identify malicious content, hosted on webservers. The proposed hybrid system integrates active module concept of a client honeypot into a server honeypot. The active module interacts with webservers utilising a custom crawler and browser, publicises the honeypotâs IP address and therefore improves exposure of server honeypot's vulnerable services. The findings presented in this paper show that interaction with webservers improves exposure, and results in significantly higher number of attacks, which in turn, increases the probability of discovering new threats. The findings also characterise most attacks to be worm based and directed at Windows based hosts and services.